Sphingomyelinases D From Loxosceles Spider Venoms and Cell Membranes: Action on Lipid Rafts and Activation of Endogenous Metalloproteinases - Lopes, Priscila Hess; Berg, Carmen W. van den; Tambourgi, Denise V. (Frontiers in Pharmacology, 2020)
Loxosceles spider venom contains Sphingomyelinase D (SMase D), the key toxin causing pathology. SMase D hydrolyzes the main component of lipid rafts, sphingomyelin, which changes the membrane microenvironment resulting in the activation of endogenous metalloproteinase from the ADAMs family. Alterations in membrane microenvironment of lipid rafts contribute to the activation of several cell surface molecules. Serine proteinases convertases acting on the pro-domain of membrane metalloproteinases, such as ADAMs, increase the cleavage and the release of proteins ectodomains and receptors located at the cell surface areas containing lipid rafts. We, therefore, investigated the interaction of SMases D with these membrane microdomains (lipid rafts) in human keratinocytes, to better understand the molecular mechanism of SMases D action, and identify the ADAM(s) responsible for the cleavage of cell surface molecules. Using specific inhibitors, we observed that ADAMs 10 and 17 are activated in the cell membrane after SMase D action. Furthermore, proproteins convertases, such as furin, are involved in the SMase D induced ADAMs activation. One of the signaling pathways that may be involved in the activation of these proteases is the MAPK pathway, since phosphorylation of ERK1/2 was observed in cells treated with SMase D. Confocal analysis showed a strong co-localization between SMase D and GM1 ganglioside present in rafts. Analysis of structural components of rafts, such as caveolin-1 and flotillin-1, showed that the action of SMase D on cell membranes leads to a reduction in caveolin-1, which is possibly degraded by toxin-induced superoxide production in cells. The action of the toxin also results in flotilin-1 increased detection in the cell membrane. These results indicate that SMases D from Loxosceles venoms alter membrane rafts structure, leading to the activation of membrane bound proteases, which may explain why the lipase action of this toxin can result in proteolytic cleavage of cell surface proteins, ultimately leading to pathology.